The Effect of PAI Learning and Discipline of Worship on the Islamic Character of Elementary Education Level Students - Lubis, Chairul Azmi; Daulai, Afrahul Fadhila; Hasibuan, Humaidah Br. (Jurnal Basicedu, 2022)
This study aims to determine the effect of PAI learning and the discipline of worship on the Islamic character of elementary education students. This study uses a quantitative approach with experimental methods. The population of this research is the students of the integrated Islamic school Khairul Imam as many as 157 students, with a total sample of 60 students. The data collection instrument was in the form of multiple choice tests, namely Pretest & Posttest, and a questionnaire in the form of a scale. The results of the study show: First, the influence of PAI learning on the Islamic character of students. Accordingly, there is an influence between the pre-test and post-test of PAI learning on the Islamic character of students, which is 57%. Second, the influence of the discipline of worship on the Islamic character of students. In connection with that, there is an influence between the pre-test and post-test of the discipline of worship on the Islamic character of students is 40%. Third, the influence of PAI learning and the discipline of worship on the Islamic character of students. In connection with that, there is an influence between the pre-test and post-test of PAI learning and the discipline of worship on the Islamic character of students is 21%.